Effectiveness of the Self-Instructional Module (Sim) On Knowledge and Attitude Regarding Cervical Cancer and Human Papilloma Virus Vaccination among Adolescent Girls - Amruta Anand Mhalungekar; Chandrala S Patole; Manisha A Bijapurkar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
BACKGROUND AND OBJECTIVES: Good Health and well-being are the most essential things in life. It is a very important and precious asset that one should treasure, and to enjoy life to the fullest, one must take steps to prevent disease and illness. According to the National Cancer Registry Program (ICMR-NCRP), there were an expected 3.4 lakh cases of cervical cancer in the nation in 2023 3.4 lakh. Over one million children lose their mother to cancer every year, and 1.4 million lose their father. In the year 2022, some 9.6 million people died of cancer, and it is anticipated that by 2030, this number will rise to 13.2 million. World Health Organization’s focus is to prevent cervical cancer to accelerate its elimination globally, the prophylactic Human Papilloma Virus vaccination has been a foundational pillar of the WHO Global Strategy. It is estimated that the implementation of this strategy can help in the prevention of 60 million cervical cancer cases and 45 million deaths in the upcoming 100 years. So, the investigator has planned to evaluate the knowledge and attitude of adolescent girls on cervical cancer and Human Papilloma Virus vaccination. The aim of the present study is to identify the knowledge and attitude regarding cervical cancer and Human Papilloma Virus vaccination. OBJECTIVES OF THE STUDY: THE present study aimed to evaluate the effectiveness of the Self-Instructional Module (SIM) on knowledge and attitude regarding cervical cancer and Human Papilloma Virus (HPV) vaccination among adolescent girls studying in Kamala college of Kolhapur. The objectives are as follows: 1) To evaluate the effectiveness of the self-instructional module (SIM) on knowledge and attitude regarding cervical cancer and Human Papilloma Virus vaccination among adolescent girls. 2)To find out the correlation between pre-test knowledge and attitude scores regarding cervical cancer and Human Papilloma Virus vaccination. 3) To find out an association between pre-test knowledge and attitude scores regarding cervical cancer and Human Papillomavirus vaccination among adolescent girls with their selected socio-demographic variables. The sample size of the present study consisted of 78 adolescent girls. METHODS: A pre-experimental one-group pre-test post-test design with a quantitative evaluative survey approach was adopted. Ethical clearance was obtained from the Institutional Ethics Committee of D. Y. Patil Education Society (Deemed to be University), Kolhapur, and prior permission was secured from the Principal of Kamala College, Kolhapur. The study was conducted among 78 adolescent girls aged 15–18 years, selected through purposive sampling. Data were collected using a structured knowledge questionnaire (28 multiple-choice items) and a structured attitude scale (20 Likert items) on cervical cancer and Human Papilloma Virus (HPV) vaccination. A pre-test was conducted on Day 1, after which the Self-Instructional Module (SIM), prepared by the researcher and containing information on cervical cancer and HPV vaccination, was administered. The post-test was carried out on Day 7.Data were analyzed and tabulated systematically. RESULTS: In the pre-test, 56 (71.8%) subjects had average knowledge, and 22 (28.2%) had poor knowledge. Post-test results showed improvement, with 58 (76.9%) having average knowledge, 16 (20.5%) good, and 2 (2.6%) poor knowledge. Regarding attitude, 48 (61.5%) had unfavorable and 30 (38.5%) moderately favorable attitudes in the pre-test. In the post-test, 55 (70.5%) had moderately favorable, 19 (24.4%) favorable, and only 4 (5.1%) had unfavorable attitudes. In the present study, a significant correlation (p < 0.01) was found between pre-test knowledge and attitude scores on cervical cancer and HPV vaccination and the selected socio-demographic variables. There was a significant association between the pre-test knowledge scores of the subjects with their selected socio-demographic variables at a 0.05 level of significance. There was a significant association between the pre-test attitude scores of the subjects with their selected socio-demographic variables at a 0.05 level of significance. INTERPRETATION AND CONCLUSION: The study concluded that the self-instructional module (SIM) was effective in increasing the knowledge and enhancing a positive attitude towards cervical cancer and Human Papilloma Virus vaccination among the subjects of Kamala College, Kolhapur.